Respon Beberapa Pupuk Bokashi Padat Terhadap Hasil Produksi Tanaman Cabai Rawit Hiyung - Chusnul Chotimah; Antar Sofyan; Tuti Heiriyani (Agroekotek View, 2020)
Types of vegetables that have a spicy taste with small and distinctive fruits, namely types of vegetables Chili pepper (Capsicum frutescens L.) which is one of the horticultural plants. Chili pepper in Indonesia is popular as ingredients for making various condiments and traditional cooking seasoning. Chili pepper also used for making medicine such as patch and analgesic, besides containing spicy (capsicin) substance, also contain provitamin A and vitamin C. The cultivation of Hiyung Chili at their hometown (village Hiyung) is done on plot during the dry season, but the chili pepper also grow on dry or rainfed land. An average productivity of chili pepper on South Kalimantan is 3.7 ton/ha, while the potential is around 8 ton/ha. Therefore, the cultivation of Hiyung chili has the potential to be developed in various types of land and increased productivity with cultivation technology improvements by fertilization can be a support for generative growth that leads to good production and quality results. Bokhasi fertilizer can provide a good response so that it functions to improve soil fertility because it can support the availability of nutrients such as S, N, K, P Ca, and Mg and make soil permeability better. This research use randomized block design with 1 factor and 4 replication, solid bokashi fertilizer application consist of 6 treatments, k0=control+0,04 kg NPK; k1=1,2 kg kirinyuh+0,04 kg NPK; k2=1,2 kg husk+0,04 kg NPK; k3=1,2 kg city wasted+0,04 kg NPK; k4 = 1,2 kg gamal leaf+0,04 kg NPK; k5=1,2kg. water hyacinth+0,04 kg NPK. The research indicated that several kinds of solid bokhasi fertilizer effect very significantly on all parameters such as harvest age, amount of fruit, fresh fruit weight and crop production tons /ha. Treatment with the best effect on Hiyung chili pepper plant production results is k3 (city wasted + NPK).